Incorporating Indigenous Knowledge into Chemistry Lessons on Acids and Bases: : Exploring Potential and Challenges - Simasiku, Fredrick Simataa; M. Ngcoza, Kenneth (Universitas Terbuka, 2024)
This study delved into the potential and hurdles involved in integrating indigenous knowledge (IK) into Physical Science lessons among Namibian teachers. Rooted in an interpretive paradigm, it adopted a qualitative case study approach, gathering data through observations and stimulated recall interviews. Socio-cultural theory served as the overarching framework, with Pedagogical Content Knowledge (PCK) used as a lens for data analysis. Specifically, the study employed five knowledge components within the realm of topic-specific pedagogical content knowledge (TSPCK) to scrutinize the data. Two Grade 9 Physical Science teachers were observed teaching concepts on Acids and Bases, with each teacher's two lessons providing qualitative data. Teachers were purposively sampled for inclusion in the study. The findings indicated that teachers possessed local knowledge that could be effectively integrated into Physical Science topics. For example, the topic of acids and bases was identified as conducive to incorporating IK. Both observed teachers utilized local substances to enable learners to practically test them using litmus paper (blue or red). Substances such as Omutoko (wood ash), Oshikundu (a traditional drink made from Mahangu flour and sorghum), Oshimhumu (a shrub used for dental hygiene), and Onghalanyenye (subterranean soil) were tested for their acidic or alkaline properties during Physical Science lessons. Stimulated recall interviews further revealed teachers' awareness of homegrown substances suitable for teaching acids and bases in science lessons.